Study guides

☆☆

Q: What does the m equal in the equation -6 equals 8-2m?

Write your answer...

Submit

Still have questions?

Related questions

t is equal to 6

3/2(1-5)=-6 3/2(-4)=-6 3/-8=-6 Not equal. This equation is a false equation. Unless a variable was meant to be in the equation, this equation is not equal.

There is no "answer", X=6 is complete in itself. There is nothing to solve. What is the value of X? Well, it's equal to 6.

2x must equal 12 so x is 6.

The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.

The first equals the second because they're the same total on each side of the equals sign. Try it with grapes, then you can eat your equation.

9x + 4 = 6 9x = 6 -4 9x = 2 x = 2/9

You have not given us an equation, just a term, x + 6. Every equation states that some quantity is equal to some other quantity, and this is shown by means of the equals sign (=). An example of this might be, x + 6 = 10. If that was the equation, then x = 4.

It is an equation ... Anything with an equals is an equation 2+b=6 Anything without an equals is an expression 2+a

The equation 6 + y = 12 is a simple equation in one variable. If you add 6 to both sides of the equals sign, you get y = 18, and that is the solution.

It is not possible to solve a single linear equation in two variables.

That's not an equation, it has no equal sign. It seems that when typing a question, the equal sign and some other signs get eliminated on this site; you'll have to write the equal sign as "equals" or "equal"; similarly for some other special symbols.

It is an equation because: a = 6

No because in this equation x = -6 -6--6 = 0

Yes. Anything = anything is an equatiton

the answer of this complicated equation equals ten

x=6

x=6

t= -6

This is called an equation....

No.

What does 6+4 equal?It equals 10.

I believe the converse is: if 2x equals 6 then x equals 3 inverse: if x doesn't equal 3 then 2x doesn't equal 6 contrapositive: if 2x doesn't equal 6 then x doesn't equal 3

-47

hujkImproved anwser:2x+6 = 7x-42x-7x = -4-6-5x = -10x = 2